1995
DOI: 10.1111/j.1460-2695.1995.tb01192.x
|View full text |Cite
|
Sign up to set email alerts
|

Fatigue Crack Growth and Closure at High Stress Ratios

Abstract: Fatigue crack growth tests have been carried out on a medium carbon structural steel over a wide range of stress ratios, i.e. from 0 to 0.7. All tests were conducted under constant amplitude loading conditions corresponding to growth rates in the Paris regime. Crack closure behaviour was observed experimentally by a surface strain gauge technique, and numerically by a finite element analysis under plane stress condition. While the crack closure could not be detected by experimental measurements at stress ratio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 28 publications
1
17
0
Order By: Relevance
“…In measurements referred to earlier, Tsukuda et al 7 . failed to detect crack closure at R ≥ 0.5, although their FEM analyses did indicate the occurrence of this mechanism for R ‐ratios up to 0.7.…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…In measurements referred to earlier, Tsukuda et al 7 . failed to detect crack closure at R ≥ 0.5, although their FEM analyses did indicate the occurrence of this mechanism for R ‐ratios up to 0.7.…”
Section: Discussionmentioning
confidence: 83%
“…have observed that the d a /d N versus Δ K eff data are still considerably separate for each positive R ‐ratio, the shift of a given plot in the positive direction of the Δ K eff axis increasing with the R ‐value. Results like those presented in Refs [6–8] are likely to imply that the CC concept cannot sufficiently account for the R ‐ratio influence on crack growth. However, Toyosada and coworkers (Toyosada et al unpublished observations) did obtain a good correlation of the d a /d N versus Δ K eff data from different positive R ‐ratio tests on specimens of the same material and geometry as those used by Skorupa et al 8…”
Section: Introductionmentioning
confidence: 73%
See 3 more Smart Citations